Estudio de factibilidad para la creación de un restaurante de platos típicos lojanos en la ciudad de Quevedo año 2012 - Flores González, Favio Fernando (2012)
The academic foundation of the profession of Management generates entrepreneurship initiatives, which together with the investigator's decision, prompted establish knowledge about selling food Loja. It is our professional baseline and experience directed at the food court, an activity that has been developing for many years research. Your application will be evidenced by structuring, organizing and creating a company with sales of restaurant dishes Loja and develop a business proposal for the creation of a restaurant in the city of Quevedo, from the year 2012. It consolidates project information with methodological structuring and gathering knowledge and techniques serving to demonstrate the feasibility of the feasibility study, focused as an application for economic and poductive development of an enterprise. The feasibility study aimed at creating a lojanos restaurant dishes, will satisfy a wide range of market and promote economic profitability a company in the city of Quevedo, from the year 2012. Thus fulfilling the objectives of the project and with the hypothesis suggested.